Periodontitis and peri‐implantitis in elderly people experiencing institutional and hospital confinement - Müller, Frauke; Srinivasan, Murali; Krause, Karl‐Heinz; Schimmel, Martin (Periodontology 2000, 2022)
An increasing number of elderly people retain their natural teeth into old age and further, the prevalence of endosseous implants for supporting oral prosthesis is ever increasing. These teeth and implants now present a considerable challenge in terms of maintenance, especially when patients become dependent on care. Periodontal and peri‐implant diseases are more prevalent in elderly than in younger age cohorts. There are distinct differences related to the inflammatory response between periodontal and peri‐implant tissues, both in young and old age. The age‐related reasons for the increase in periodontal infections may be related to poor oral hygiene because of a loss of dexterity or vision, but also to immunosenescence. This term describes the aging of the immune system and the decline of its effectiveness with age. Low‐grade infections, like chronic periodontitis, may cause low‐grade inflammation and subsequently increase the likelihood of developing chronic diseases. In return, treatment of periodontitis may improve general health, as demonstrated for diabetes. A second mechanism illustrating how poor oral health translates into systemic disease is the risk of developing aspiration pneumonia. The treatment options in old age should be evaluated with regard to the issues of general health and maintenance. Systematic periodontal maintenance therapy, as performed in younger age cohorts, may be difficult to implement in elderly people experiencing institutional or hospital confinement because of logistics, barriers related to patients and caregivers, or cost. The scale of periodontal disease in old age represents a public health issue.